Microteaching: Methodology for the Development of Skills in Teacher Training in Educational Sciences. Perception of the Students of the University of Costa Rica: La microenseñanza: metodología para el desarrollo de habilidades en la formación docente en ciencias de la educación. Percepción del estudiantado de la Universidad de Costa Rica (Papeles, 2023)
Introduction: Microteaching is a strategy of simulation of the professional task for the development of skills, in this case, it is a teaching process that, subsequently, is analyzed in order to reflect on actions that lead to the improvement of Costa Rican education. The purpose of this study is to describe the perceptions of the student body participating in the simulation of a class to determine the benefits and contributions it provides to teacher training. Methodology: 40 teacher training students participated in the workshop; it was carried out in three phases: first, planning, then execution, and finally, feedback of the process. Results and discussion: The information obtained and analyzed revealed as areas of interest, the planning of a class, educational practice, group management in the classroom and the contribution of microteaching to the teaching task, which were experienced through the integration of theory and practice. Conclusions: In response to the problem question, What is the contribution in teacher training? the study concludes that, students require praxis for their training and, microteaching has proven to be a didactic strategy that allows the development of teaching skills and ensures deep learning by means of autoscopy during feedback; therefore, it invigorates the formative process of the students and the University.
Keywords: Educational practice; teaching method; learning; teacher training; higher education